The Roles of Human, Nature, and Supernatural Power in Phuoc's The Celestial King Phu Dong and the Iron Horse - Manggala, Simon Arsa (Journal of Language and Literature, 2023)
Anthropocentrism centralizes the role of humans and human impact on the environment. In folktales, the anthropocentric nuance is amplified by the moral messages delivered after telling the tales. The moral messages are usually for the betterment of humans. This paper intends to offer an alternative reading of a folktale by shifting the focal perspective slightly from human to nature and supernatural beings and their power. The object of this paper is a folktale from Vietnamese culture titled The Celestial King Phu Dong and the Iron Horse. In the tale, the human character could defeat the monster since they had supernatural power. This paper employs three tools to foreground the roles of nature and supernatural power. The folktale's plot is analyzed by its tale elements proposed by Booker (2004). The power relation of the actants is analyzed using Greimas' actantial analysis, and the clause structure is examined by Systemic Functional Linguistic's thematic structure analysis. The result shows that the plot is built upon the opposition between human and nonhuman characters. The actantial analysis indicates that in opposing the nonhuman character, the human character needs help from nature and supernatural power. The thematic patterns structure the delivery of the power relation and the human character dependency. This paper concludes that human character is depicted as dependent on nature and supernatural power in solving problems and obstacles. It foregrounds the agency of objects surrounding humans.